Production rights in European agriculture - Barthelemy, Denis; David, Jacques (INRA Editions ; Elsevier, 2001)
Rather than simply cataloging the various interpretations of European regulations by Member States, this international team examines the economic priorities, the legal bases, the social norms and cultural patterns which come into play, presenting an analytical approach to the study of production rights in European agriculture. This work traces the emergence and the economic and legal content of the different income support tools for agricultural producers, collectively termed 'production rights' and it looks at the foundations of the specific national conceptions underlying the methods of organising agricultural activity. The book is intended for a varied readership: farmers themselves, of course, but also economic, legal and tax consultants, experts, lawyers, notaries, as well as students, teachers and researchers. It has been set out in such a way as to allow readers to move freely from one subject to another, depending on whether their interest lies in economic aspects or legal developments, or whether they are more concerned by certain production rights or by certain features of their own organisation. The goal of the book is to enable the reader to grasp the special features and the significance of the forces which have shaped the current income support instruments for producers in the various Member States of the EU, and which will unquestionably continue to influence the measures which flow from reforms to the Common Agricultural Policy in the years to come.